Mathematical modelling for infectious viral disease: The Covid-19 perspective - Hafeez A. Adekola; Ibrahim A. Adekunle; Haneefat O. Egberongbe; Sefiu A. Onitilo; Idris N. Abdullahi (African Governance and Development Institute (AGDI), 2020)
In this study, we examined various forms of mathematical models that are relevant for the containment, risk analysis and features of COVID-19. Greater emphasis was laid on the extension of the Susceptible-Infectious-Recovered (SIR) models for policy relevance in the time of COVID-19. These mathematical models play a significant role in the understanding of COVID-19 transmission mechanisms, structures and features. Considering that the disease has spread sporadically around the world, causing large scale socioeconomic disruption unwitnessed in contemporary ages since World War II, researchers, stakeholders, government and the society at large are actively engaged in finding ways to reduce the rate of infection until a cure or vaccination procedure is established. We advanced argument for the various forms of the mathematical models of epidemics and highlighted their relevance in the containment of COVID-19 at the present time. Mathematical models address the need for understanding the transmission dynamics and other significant factors of the disease that would aid policymakers to make accurate decisions and reduce the rate of transmission of the disease.
Keywords: 330; Mathematical Models; SIR Models; COVID-19; COVID-19 confirmed cases; COVID-19 attributable deaths